2020
DOI: 10.1590/1414-462x202028010181
|View full text |Cite
|
Sign up to set email alerts
|

Influência do consumo alimentar e da prática de atividade física na prevalência do sobrepeso/obesidade em adolescentes escolares

Abstract: Resumo Introdução A adolescência é definida pela Organização Mundial da Saúde como a faixa etária de 10 a 19 anos, pois é nessa fase em que são observadas diferentes mudanças. Objetivo Analisar a existência de associação entre sobrepeso/obesidade e fatores de risco em adolescentes escolares. Método Estudo transversal, conduzido nas escolas de nível médio, da rede pública estadual, na cidade de Sobral, no Ceará, com amostra de 572 jovens. Os dados foram coletados utilizando questionário semiestruturado, IPAQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
14

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 29 publications
0
10
0
14
Order By: Relevance
“…In relation to practicing physical activity, a research study conducted in Piauí with adolescents aged between 13 and 19 years old identified that the level of physical activity characterized as active was 12.6% 26 , lower than that found in this study. It is believed that the increasingly frequent practice of sedentary leisure and the fast technological development of the past few years, characterized by the increased time spent on electronic games, computers, television and cellphones, reduce the adolescents' interest in activities that provide energy expenditure 2,27 . It is important to highlight that the practice of physical activity among adolescents implies the improvement of general well-being, mental health and prevention of chronic non-communicable diseases, with governmental measures and of the society as a whole being indispensable to prevent sedentary lifestyle in the young population 2 .…”
Section: /13mentioning
confidence: 99%
See 2 more Smart Citations
“…In relation to practicing physical activity, a research study conducted in Piauí with adolescents aged between 13 and 19 years old identified that the level of physical activity characterized as active was 12.6% 26 , lower than that found in this study. It is believed that the increasingly frequent practice of sedentary leisure and the fast technological development of the past few years, characterized by the increased time spent on electronic games, computers, television and cellphones, reduce the adolescents' interest in activities that provide energy expenditure 2,27 . It is important to highlight that the practice of physical activity among adolescents implies the improvement of general well-being, mental health and prevention of chronic non-communicable diseases, with governmental measures and of the society as a whole being indispensable to prevent sedentary lifestyle in the young population 2 .…”
Section: /13mentioning
confidence: 99%
“…In 2016, 18% of the children and adolescents in the world, aged between 5 and 19 years old, presented excess weight 1 . In the Brazilian Northeast region, specifically in Ceará, a study conducted with 572 adolescents aged between 10 and 19 years old evidenced a 20% prevalence of excess weight 2 . In Minas Gerais, in a research study conducted with 70 students with mean age of 16.4 years old, the prevalence of overweight/ obesity was of 24.3% 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esse conjunto de fatores é atribuído a maiores riscos para o surgimento e a precocidade de doenças crônicas e complicações metabólicas, como dislipidemias, hipertensão arterial, dentre outras morbidades (Barbalho et al, 2020).…”
Section: Introductionunclassified
“…A Organização Mundial da Saúde (OMS) define a adolescência como a faixa etária de 10 -19 anos, no mundo 20% da população estão nessa faixa etária, enquanto no Brasil são 17%, totalizando 34 milhões de pessoas (Barbalho et al, 2020).…”
Section: Introductionunclassified